CHORISPORA TENELLA (PALL.) DC. (BRASSICACEAE), NUEVO REGISTRO PARA LA FLORA ADVENTICIA DE CHILE - Teillier, Sebastián; Prina, Aníbal; Romero, Fernanda (Gayana Botánica, 2007)
Chorispora tenella (Pall.)DC., is registered for first time for Chilean territory as an alien species. A brief description and illustration is given. The specimens here cited were collected at the Yeso valley, at 2400 m altitude (33°41’S - 70°06’W).